Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T20:58:55+01:00
(m+n)(m-2)+(m-n)(m+1)=m²-2m+mn-2n+m²+m-mn-n = 2m²-m-3n

(3x-2)(3x-2y+1)-4x(2x-3y+1)= 9x²-6xy+3x-6x+4y-2-8x²+12xy-4x= x²+6xy-7x+4y-2

3(m+1)(n-2)+2(n+1)(m-2)=(3m+3)(n-2)+(2n+2)(m-2)= 3mn-6m+3n-6+2mn-4n+2mn-4n= 7mn-6m+3n-6

x(x+1)(x+2)-x(x-1)(x-2)=(x²+x)(x+2)-(x²-x)(x+2)=x³+2x²+x²+2x-x³+2x²-x²-2x
2 5 2
2009-11-19T20:59:16+01:00
A)(m+n)(m-2)+(m-n)(m+1)=m²-2m+mn-2n+m²+m-mn-n=2m²+m-2n

b)(3x-2)(3x-2y+1)-4x(2x-3y+1)=9x²-6xy+3x-6x+4y-2-8x²+12xy-4x= x²+6xy-7x+4y-2

c)3(m+1)(n-2)+2(n+1)(m-2)= 3mn -6m +3n -6+2n²-4m+2n-4 = 3mn -10m+5n+2n²-10

d)x(x+1)(x+2)-x(x-1)(x-2)= x(x²+2x+x+2)-x(x²-2x-x+2) = x³+2x²+x²+2x-x³+2x²+x²-2x = 6x²
3 3 3